1987
DOI: 10.1177/003072708701600302
|View full text |Cite
|
Sign up to set email alerts
|

Yam Production and its Future Prospects

Abstract: The yam is an important food crop, especially in the so-called ‘yam zone’ of West Africa: total world production is about 19 million tonnes per annum, some 70 per cent of it grown in Nigeria. Although regarded as mainly a source of carbohydrate, some species are nearly as rich in protein as rice or maize. The increasing acceptability of smaller tubers provides an opportunity for extending the area of cultivation but much more research is still needed on methods of propagation, disease control, and post-harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 0 publications
2
59
0
Order By: Relevance
“…This result is in line with other research reports which indicated nutritional content of yam varies with species [14]. It is also indicated that, the mean protein content of aerial yam is higher than the protein value of sweet potato, potato, cassava, taro and plantain [15]. Similarly, It is reported that presence of higher protein contents in yam tuber compared to other tropical root and tuber crops like cassava, sweet potato and taro which highlight its' nutritional superiority as a staple food [10; 14; 16; 17].…”
Section: Proximate and Mineral Composition Variability Among Yam (Diosupporting
confidence: 92%
“…This result is in line with other research reports which indicated nutritional content of yam varies with species [14]. It is also indicated that, the mean protein content of aerial yam is higher than the protein value of sweet potato, potato, cassava, taro and plantain [15]. Similarly, It is reported that presence of higher protein contents in yam tuber compared to other tropical root and tuber crops like cassava, sweet potato and taro which highlight its' nutritional superiority as a staple food [10; 14; 16; 17].…”
Section: Proximate and Mineral Composition Variability Among Yam (Diosupporting
confidence: 92%
“…The techniques of product development from both views indicate that product development does not exist in a vacuum [3]. They have three principles of defend, extend and build.…”
Section: Introductionmentioning
confidence: 99%
“…Ghana is one of the most important yam producing countries in the world; it is the third (9%) behind Nigeria (66%) and Cote d'Ivoire (13%) in terms of production (FAO, 2009). It is an elite crop, preferred over other root and tuber crops in West Africa and it is the food of choice at festive occasions, and the only crop that is celebrated wherever it is cultivated (Coursey, 1967;Hahn et al, 1987). Resource poor people, especially women, derive a good income from its production, processing, and marketing (Dufie, 2009).…”
Section: Introductionmentioning
confidence: 99%